Associations of daily step counts with depressive symptoms during pregnancy: Ruian birth cohort study - Wenyi Zhang; Qiuqiu Mu; Peijun Chen; Yinyin He; Yexinyi Zhou; Jiawei Fang; Chenjun Tang; Jing Guo; Wenjun Du; Lin Lin; Guangdi Chen (BMC Public Health)
Abstract Background Although studies have shown that physical activity may have protective effects against depression during pregnancy, evidence on the role of objectively measured physical activity remains limited. This study aimed to explore the associations between daily step counts in the second trimester and depressive symptoms at different stages of pregnancy. Methods Based on 828 pregnant women from the Ruian Birth Cohort Study, daily step counts were averaged over a week from WeChat records in the second trimester. Linear and logistic regression models were used to evaluate associations of daily step counts in the second trimester with Edinburgh Postnatal Depression Scale (EPDS) scores and clinically significant depressive symptoms (EPDS scores ≥ 10) in the second and third trimesters, respectively. Results The 828 pregnant women took an average of 3,840 (± 2,170) steps each day in the second trimester. Higher daily step counts were associated with lower EPDS scores in both the second (a unit of 1000 steps; β: -0.16, 95% CI: -0.30 to -0.03) and third trimesters (β: -0.25, 95% CI: -0.40 to -0.10). Additionally, higher step counts correlated with lower odds of clinically significant depressive symptoms in the third trimester (OR: 0.88, 95% CI: 0.79 to 0.96). The benefits were consistent across weekends and workdays. Conclusion Distinct patterns of association between second-trimester daily step counts and depressive symptoms in the second and third trimesters highlight the potential mental health benefits of maintaining higher daily step counts. The accessibility and high user engagement make daily step counts as a particularly practical tool for monitoring physical activity during pregnancy.